Efficacy of cumulative cisplatin dose on survival in patients with locally advanced cervical cancer treated with definitive chemoradiotherapy: multicenter study by Turkish Oncology Group - Akyildiz, Arif; Gultekin, Melis; Yigit, Ecem; Demir, Ecem; Ismayilov, Rashad; Ahmed, Melin; Arik, Zafer (Elsevier, 2024)
Objective To investigate the impact of cumulative cisplatin dose on clinical outcomes in locally advanced cervical cancer patients undergoing definitive chemoradiotherapy. Methods A retrospective analysis was conducted on 654 patients with stage IB3-IVA disease treated with definitive chemoradiotherapy. Radiotherapy was applied as external beam pelvic with or without para-aortic radiotherapy and brachytherapy. Concomitant chemotherapy was in the form of weekly or 3 weekly cisplatin. Data on demographics, treatment protocols, cumulative cisplatin dose, adverse effects, and survival outcomes were collected. Statistical analyses, including univariate and multivariate Cox regression models, were used to assess factors influencing progression free survival and overall survival. Results The median cumulative cisplatin dose was 210mg (range 40-320), and >= 200mg in 503 (76.9%) patients. Median follow-up was 35 months (range 1-150). The 5year progression free survival and overall survival rates were 66.9% and 77.1%, respectively. Multivariate analysis identified poor performance status, non-squamous cell histology, presence of lymph node metastases, and hemoglobin <10g/dL before chemoradiotherapy as poor prognostic factors for both progression free survival and overall survival in the whole group. When stage III cases were evaluated separately, the cumulative cisplatin dose <200mg was found to be a significant poor prognostic factor in overall survival (hazard ratio 1.79, 95%confidence interval 1.1 to 3.0, p=0.031). Conclusion Our study showed that a cumulative cisplatin dose >200mg, particularly in patients with lymph node metastases, significantly improved overall survival. Factors such as anemia, toxicity related challenges, and comorbidities were identified as critical considerations in treatment planning. These findings emphasize the balance between maximizing therapeutic efficacy and managing toxicity, guiding personalized treatment approaches for locally advanced cervical cancer.
Keywords: Cervical Cancer; Cervix Uteri; Radiotherapy